Vehicle routing problem for the minimization of perishable food damage considering road conditions - María Paula Buelvas Padilla; Paula Andrea Nisperuza Canabal; Jorge Mario López Pereira; Helman Enrique Hernández Ria\~no (Logistics Research, 2018)
Transportation is one of the post-harvest activities in which perishable food products may suffer mechanical damage, which translates into a substantial loss of quality and product value. The main source of this type of damage in transportation is vibration, influenced, among others factors, by road conditions, a factor that can be considered in the vehicle routing problem. To address this issue, the following article proposes a multi-objective model that seeks to minimize the mechanical damage suffered by products during transport and the distance traveled by vehicles. To evaluate the model, we examined 20 instances adapted from the literature for the vehicle routing with time windows, and we found a Pareto frontier approximation for each instance. The results allowed us to observe the relationship between the damage and the distance traveled and showed that the proposed model is capable of providing feasible routes considering trade-offs between these objectives. Hence, our model provides decision makers with a tool for an effective determination of vehicle routes that considers the damage that perishable food products may experience during transport. Finally, we present some ideas for the application of the model in larger instances as well as future research directions.
Keywords: 650; vehicle routing problem; time windows; perishable food products; mechanical damage; road conditions; multi-objective